Pharmacy Assistant Mobile Application (PAMA): Development and Reviews - Thinnukool, Orawit; Khuwuthyakorn, Pattaraporn; Wientong, Purida (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Nowadays, pharmaceutical mobile applications are widely used. Several features and functionality play an important role to support the real needs of users especially in primary medication. Users’ behaviors in the modern world have changed where users may prefer to access drug information using search engines via the Internet rather than consulting with professionals like pharmacists, doctors or experts. However, the drug information that users retrieve from the internet sources may provide inaccurate, incomplete or unreliable information. The questions are: can we decrease this phenomenon? Suppose that we are applying an application to a content provider, which application functionalities are suitable for users and support their real needs? Can the application encourage users to gather drug information via the application instead of searching via the internet sites? The proposed study aimed to develop a Pharmacy Assistant Mobile Application (PAMA) based on necessarily required features and functionalities which are designed and operate on the iOS operation system. The application performance has been tested and measured regarding the graphic user interface and the system acceptance level. The experimental results have been reviewed and an issue has been found which needs to be considered as an important factor when developing a healthcare mobile application for the real uses.